PEMODELAN JALUR PEDESTRIAN DI SEKITAR LAPANGAN BOLA PERUMAHAN TAMAN SETIA BUDI INDAH DITINJAU DARI UNSUR KENYAMANAN - Simbolon, Ridho J. S.; Pakpahan, Raimundus; Aritonang, Emmy Ria (ALUR :Jurnal Arsitektur, 2018)
The pedestrian pathway can interact socially between communities. A pedestrian should be able to ensure safety and comfort as well as aesthetic value for pedestrians. The pedestrian pathway is crucial in urban design elements, especially in areas with high activity levels. As in Taman Setia Budi Indah Football Field, the existing pedestrian path is not able to accommodate its users. Both of the pedestrian materials and pedestrian supporting elements do not meet the elements of comfort and security and aesthetic value. The researcher tries to find modeling of a pedestrian path in that area which fulfills the element of comfort, safe and aesthetic value. The research method used is a qualitative method of observation. The method is analyzed based on theoretical analysis based on the comparison of the variable that has been determined. Through the theoretical analysis found several criteria pedestrian that meets the elements of comfort. The results of the analysis are then made modeling pedestrian paths around the Football Field in Taman Setia Budi Indah in the form of additional pedestrian width and other supporting elements such as seating, lighting, bins etc. to improve the safety and comfort for the walkers and utilization of river potentials in the area such as the attraction when walking.